Development of Automated Miniature Greenhouse for Real-Time Monitoring of Environmental Parameters (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Greenhouse cultivation requires continuous monitoring of environmental and soil conditions to support plant growth. Manual monitoring can be time-consuming and may not ensure consistent control. This study developed and evaluated an automated miniature greenhouse system that monitors environmental parameters and activates devices based on preset thresholds. The system used an Arduino Uno microcontroller integrated with soil moisture, soil temperature, DHT11, LDR, and MQ gas sensors. Relay modules controlled a ventilation fan, water pump, and artificial light. Solar energy was used to support the microcontroller power supply. System evaluation included calibration testing, three-trial sensor accuracy testing, and seven-day operational monitoring.Calibration results confirmed correct wiring and proper communication between components. Accuracy testing showed consistent readings across three trials: temperature at 26°C, humidity between 54% and 55%, soil moisture averaging 28.82%, carbon dioxide at 8130 ppm, methane at 0 ppm, and light intensity averaging 31 lux. Actuators operated according to programmed conditions. During the seven-day monitoring period, temperature ranged from 25–27°C, humidity from 53–61%, and soil moisture changes triggered water pump activation on Day 7. Increased light intensity on Day 3 activated the artificial lighting system. A soil temperature sensor error was observed and requires correction. The results indicate that the system can monitor environmental conditions and perform automated control within the set parameters.